Evaluation of Frequency of Celiac Disease in Children with Idiopathic Epilepsy - Edalatkhah , Roohollah; Aflatonian, Majid; Dehghani firouzabadi, Bahareh; Fallah, Razieh (Iranian Journal of Child Neurology, 2024)
Objectives Extra gastrointestinal symptoms in celiac disease (CD), such as neurological manifestations, might be common in pediatrics. The present study aimed to evaluate the frequency of CD in children with idiopathic epilepsy. Materials & Methods In a cross-sectional study, signs and symptoms of CD were evaluated in 40 children aged 2-14 years with idiopathic epilepsy who were referred to the Pediatric Neurology Clinic of Shahid Sadoughi Medical Sciences University, Yazd, Iran. Then, serum levels of tissue transglutaminase antibody (tTG) and total IgA were measured in them. Upper gastrointestinal endoscopy and small intestine biopsy were recommended for patients with abnormal serum IgA Anti-tTG. Results Eighteen girls and 22 boys with a mean age of 5.29±2.4 years were evaluated. In this study, only three patients (7.5%) with epilepsy had abnormal serum IgA Anti-tTG and serum Total IgA. Upper gastrointestinal endoscopy and pathological examination of duodenal biopsy of those three children reported total villous atrophy (Marsh type 3). The age of onset of seizures in children with CD was more than three years, while in children without CD, 62.2% of cases were less than three years. These results indicate that CD is associated with the age of onset of seizures in children. Conclusion Due to the accompaniment of celiac with neurological manifestations, patients with neurological symptoms and gastrointestinal symptoms should be examined for celiac.